Analysis of Employee Performance in the Era of the Covid-19 Pandemic in Public Services - Rida Ratnawati; Burhanuddin Burhanuddin (Daengku: Journal of Humanities and Social Sciences Innovation, 2022)
The purpose of writing this thesis is to analyze employee performance in the Era of the Covid-19 Pandemic in Public Services for making E-KTP and Family Cards at the Rantau Pulung District Office. The research focus in this thesis discusses the quality of work results, quantity of work results, initiatives, job satisfaction, work knowledge. Data collection techniques used by making observations, in-depth interviews and documentation, for informants taken using purposive sampling techniques, this type of research is descriptive and will be analyzed qualitatively. The results of the study obtained by the author that the quality of the work of employees of the Rantau Pulung District Office in making E-KTP and Family Cards in Rantau Pulung was not in accordance with the SOP during the pandemic and there were errors in this writing. The quantity of work results has not reached the target to be achieved. The initiative of still employees is lacking in providing services for making E-KTP and Family Cards. Employee job satisfaction is already good, as can be seen from the friendly attitude of employees. Job knowledge is quite good, it can be seen from the education and ability of each employee. Supporting factors for employee performance include ability and knowledge as well as factors inhibiting employee performance, namely the lack of sophisticated technology, unstable internet networks and the lack of infrastructure available at the Rantau Pulung District Office.